Factors Influencing Customer Loyalty and Satisfaction: A Study of Perceived Price, Quality, and Experience in Fixed Broadband Industry - Simbolon, Jeanny Fransisca; Gumilang, Indra Bayu; Aulia, Afdal Baari; Sugiharto, Ong; Semedhi, Dimas Mahesa (Jurnal Pendidikan Indonesia, 2025)
The internet is one of the important elements today, where the internet can connect the entire world. The purpose of this study is to ascertain how Perceived Price, service quality, and customer experience influence the Indonesian consumers fixed broadband internet services in terms of customer loyalty and satisfaction. A quantitative methodology applying a survey method to analyze the 435 data collected from fixed broadband subscribers. Then, SPSS software was used in this research. According to a recent research study, consumer satisfaction and loyalty are significantly impacted by perceived price, customer experience, and service quality. This research shows that perceived price, service quality, customer experience has a strong effect to consumers’ satisfaction and customer loyalty; this research evidence can give insight for fixed broadband providers to design, develop and implement their strategy to retain customers. Based on the author's knowledge, not much research has been conducted, especially on fixed broadband internet services, to define more comprehensive factors like perceived price, service quality, customer experience on customer satisfaction and customer loyalty using quantitative research methods in Indonesia